Seven Brief Lessons on Magic 2019 - Delport, Khegan (2020)
Despite initial appearances, Tyson’s essay is not about “practical magick,” that is, the kind you might come across upon at a book-handler of esoterica, or perhaps at your local Thelemite support-group. It touches on the persistence of belief in occult phenomena well into our so-called “disenchanted” age, and does give hints as to why “magic” has not died down as of yet. But more basically, this is an intervention of philosophical theology, one aimed firstly at the academic culture of materialist reductionism. The upshot of this reductionism, for Tyson, is that “magical meanings and higher purposes are no longer part of practical reality or academic knowledge,” with the result being that we “have cut qualitative and spiritual wisdom off from knowledge and power” (p. ix). In response to this, Tyson offers a brief, albeit suggestive, proposal for an essentially Platonist metaphysics of “non-scientific truths” (p. vii).
Keywords: Rezension